Smart Island Lemukutan Through WebGIS Based Benthic Habitat Data Collection - Zan Zibar; Robin Saputra; Adityo Raynaldo; Supriyatno Supriyatno; Budhi Agung Prasetyo; Risko Risko; Hendrawan Hendrawan (Politeknik Negeri Batam, 2023)
Benthic habitats provide a variety of functions, both ecological and economic, for life in coastal areas and small islands. Smart islands or smart islands are currently being implemented in a number of small island developing countries with one of the challenges being technology based. One technology that can be used in management, including monitoring and supervision of resources, is the Geographic Information System (GIS). The synergy of GIS data and the help of the latest multimedia software technology is necessary to help display an interactive and easily accessible, in this case, webGIS technology. This research was carried out on Lemukutan Island which consists of 6 research stations, each of which has a distribution of coral reef location points based on coordinates. Based on the results of the analysis of the percentage of benthic habitats in the study locations ranging from bad to good categories. Furthermore, the data from field observations and analysis results are displayed on the Lemukan Island smart island website and can be accessed at https://webgissmartisland.com. Regular monitoring of coral reefs is very important and needs to be done to help input data for Smart Island Lemukutan so that it becomes a catalyst in realizing a smart island ecosystem in West Kalimantan Province by providing benthic habitat maps via webgis services and actualizing technological development in coastal areas and small islands. smart island based through the smart destination concept by integrating benthic habitat information via WebGIS services.